The Stratum V Pottery from Balâṭah (Shechem) - Lapp, Nancy L. (Bulletin of ASOR, 1985)
Stratum V at Shechem represents a limited occupation between the earliest Hellenistic levels and the latest Iron II, belonging to the end of the 6th and the beginning of the 5th centuries B. C. The Attic ware and one of the earliest coins ever found in Palestine date Stratum V rather precisely. Although almost no architectural remains have survived from the period, several surfaces, stratified debris layers, and the latest material in fills, present the Stratum V pottery corpus. Local wares (jars, jugs, bowls and kraters, cooking pots, and lamps) and the attic wares (black- and red-figured kraters, Attic cups, and lekythoi) are presented by drawings and descriptions and the development of the forms and comparative material are discussed.